2018
DOI: 10.1039/c8ta10055a
|View full text |Cite
|
Sign up to set email alerts
|

First-principles characterization of two-dimensional (CH3(CH2)3NH3)2(CH3NH3)n−1GenI3n+1 perovskite

Abstract: A novel two-dimensional Ge-based hybrid perovskite is proposed for potential optoelectronic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 55 publications
10
35
0
Order By: Relevance
“…Recently, indium selenide (InSe), a III-VI group layered metal-chalcogenide compound, is of great interest both experimentally and theoretically. The atomic layer of InSe has been reported to successfully synthesized via physical [510] and chemical methods [11–14], and the applications of InSe nanosheet on sensors [15], optoelectronics, and photodetectors have been explored. Srinivasa et al reported the fabrication of few-layer InSe photodetectors with high responsivity and a broad spectral detection from the visible to near-infrared region [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, indium selenide (InSe), a III-VI group layered metal-chalcogenide compound, is of great interest both experimentally and theoretically. The atomic layer of InSe has been reported to successfully synthesized via physical [510] and chemical methods [11–14], and the applications of InSe nanosheet on sensors [15], optoelectronics, and photodetectors have been explored. Srinivasa et al reported the fabrication of few-layer InSe photodetectors with high responsivity and a broad spectral detection from the visible to near-infrared region [6].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous calculations on (BA)2(MA)n1GennormalI3n+1 shows that its exciton binding energies range from 202 to 190, 150, and 34 meV for n = 1, 2, 3, and ∞ , respectively. [ 130 ] Tsai et al calculated the exciton binding energy of (BA)2(MA)n1PbnnormalI3n+1 at n = 3 and 4 and it was close to that of (MA)PbI3, in agreement with the absence of excitonic signatures in their optical absorption spectra. [ 39 ] This suggests that the excitons in (BA)2(MA)n1PbnnormalI3n+1 at n = 3 and 4 are nearly ionized at room temperature, leading to free carrier‐dominated charge transport.…”
Section: Propertiesmentioning
confidence: 73%
“…In prior work, our research team analyzed the origin of lead‐free 2DHP, (BA)2(MA)n1GennormalI3n+1 from DFT calculations. [ 130 ] The calculated decomposition energies range from 1.13 to 0.69 eV to 0.62 to 0.23 eV for n = 1, 2, 3, and ∞ respectively. The higher stability of 2DHPs was attributed to the higher decomposition energies than that of 3DHPs and the origin was explained from the Bader charge analysis.…”
Section: Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, various low dimensional nanomaterials have been considered as important functional materials due to their outstanding physical and chemical properties [1–25]. As a direct wide bandgap semiconductor with the bandgap of 3.37 eV at room temperature, zinc oxide has attracted much attention for its excellent optical and electrical performance [26, 27].…”
Section: Introductionmentioning
confidence: 99%